2011
DOI: 10.1007/s00418-011-0782-6
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Reinke’s crystals in normal and cryptorchid testis

Abstract: Within the human testis, Reinke's crystals are found in Leydig cells but their nature and function are poorly understood. The aim of our study was to investigate the properties of Reinke's crystals in man with the normal morphology of the testis (control group) and infertile patients diagnosed with cryptorchidism. 20 biopsies from infertile patients and six biopsies from men with regular spermatogenesis (20-30 years.) were used. Sections of the testis tissue were stained with haematoxylin and eosin and a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 59 publications
(77 reference statements)
3
20
1
Order By: Relevance
“…[28][29][30][31] In this study we re-investigated a previously reported finding that the number of RCs in undescended testes may be significantly greater than in normally descended testes. 15 We have confirmed a high number of RC-containing LCs in patients with a history of undescended testes, and revealed an interesting pattern of an increasing proportion of the RC-containing cells with the more cranial testis position and with significantly greater abundance of RCs in intra-abdominal testes. This is in line with influence of temperature, suggested by Kozina's study.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…[28][29][30][31] In this study we re-investigated a previously reported finding that the number of RCs in undescended testes may be significantly greater than in normally descended testes. 15 We have confirmed a high number of RC-containing LCs in patients with a history of undescended testes, and revealed an interesting pattern of an increasing proportion of the RC-containing cells with the more cranial testis position and with significantly greater abundance of RCs in intra-abdominal testes. This is in line with influence of temperature, suggested by Kozina's study.…”
Section: Discussionsupporting
confidence: 72%
“…This is in line with influence of temperature, suggested by Kozina's study. 15 Surprisingly, in our study testes that were cryptorchid at birth, and especially unilaterally undescended testes, seemed to contain higher numbers of RCs as compared to normally descended testes in TDS patients. It was unexpected because the specimens from men with a history of cryptorchidism often contain LC micronodules.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Their arrangement seems to support building of a larger crystal from smaller, immature forms. 39 In specimens originating from control biopsies we were able to establish a certain difference in number of Reinke´s crystals in perivascular and peritubular Leydig cells. Although not statistically significant, our stereological data indicated a lower number of crystals in peritubular cells.…”
Section: Discussionmentioning
confidence: 83%
“…In order to calculate the above-mentioned relative variable, appropriate formulae for numerical density have been applied. [35][36][37][38][39] The total number of crystals was determined by multiplying the testis volume (determined by the ultrasound examination) and numerical density. …”
Section: Morphometric (Stereological) Analysismentioning
confidence: 99%